Penerapan Ontologi dan Algoritma Genetika Dalam Sistem Rekomendasi Buku - Pratama, Qaris Ardian; Wibawa, I Gede Arta; Putra, Ida Ayu Gde Suwiprabayanti; Darmawan, I Dewa Made Bayu Atmaja (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 2 (2024): JELIKU Volume 13 No 2, November 2024DO - 10.24843/JLK.2024.v13.i02.p19, 2025)
This research aims to develop a website-based recommendation system to simplify the book selection prcess by combining ontology and genetic algorithms. Ontology aids users in searching for desired books more easily, while genetic algorithms provide recommendations mathcing user preferences. The study results indicate that this approach significantly assists in book selection, with 87.5% of respondents finding the recommendation aligned with their preferences. Consequently, the system reduces users’ uncertainty in choosing books, as confimed by positive feedback from respondents.